Expected clinical responses due to self-medicated Sudanese children; a pharmacological and family-medicine overview - M. I, Abdelgadir (International Journal of Medicine, 2024)
This descriptive cross-sectional study was carried in Mohammed Alameen Hamid and Jaafar bin Auf Pediatrics Hospitals in Khartoum state, Sudan. This study was conducted from March to June 2021. The study respected confidentiality using a Unique Patient Identifier (UPI) code; the questionnaires were anonymous and included no personal identifiers. Consent forms were linked to the study participant using the UPI. 33.9% of the children were self-medicated with analgesics, the route of administration for 58.4% of them was oral, 54.5% of them were using the medications until the complains disappear. 51%of the mothers reported that they were using the medications three timed daily. 37.4% of the participants reported that the fever is one of the Clinical indications for self-medication, where as 30.3% of they reported common cold. All study results showed a significance level of (p<0.05).